ENHANCING ELEMENTARY SCHOOL STUDENTS' LEARNING ACTIVITIES AND OUTCOMES THROUGH THE APPLICATION OF THE PROBLEM-BASED LEARNING MODEL - Rahmad, Rahmad (Universitas Tanjungpura, 2025)
This study was designed to address the issue of low active participation and learning outcomes among sixth-grade students at MIN III Pontianak in the IPAS subject through the implementation of the Problem-Based Learning (PBL) model. The background for this research was the persistence of a teacher-centered learning process, which led to suboptimal student engagement. Applying the Classroom Action Research (CAR) methodology based on the Kemmis and McTaggart model, this study was carried out over two cycles involving 35 participants. Data collected through observations and tests indicated significant progress: student learning activity increased from 65% in the first cycle to 85% in the second cycle. Meanwhile, the rate of classical learning mastery also jumped from 45.71% to 82.86%. Consequently, it was concluded that the PBL model is an appropriate instructional solution for tackling the problem of low student involvement and for shifting the learning paradigm towards a more active and student-centered approach in elementary education. It is recommended that teachers, particularly at the elementary level, adopt the PBL model to create participatory learning while actively assuming the role of facilitators to ensure equitable engagement from all students. This implementation would be more effective with support from the school administration through facilitating training and providing relevant learning resources. Furthermore, for future researchers, there is an opportunity to develop this study by investigating the impact of PBL more deeply on higher-order thinking skills or by testing it in the contexts of different subjects and educational levels to broaden the validity of the findings.